A Study of Virtual Machine Resource Scheduling Algorithms in Cloud Computing Environment - Tantri, Divya; George, Karan; Rajarajeswari, S (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a fast-growing technology that is being used extensively in the market today. Most cloud service providers, provide clients with one of two things either resources or services as entitled to the client by the SLA. In resource allocation a user may want to gain access to multiple resources at the same time, thus we require a method for the optimal provision of resources. With the sudden massive growth in cloud computing there is no dearth of techniques and algorithms that can be used for resource allocation. In this paper we will study the various resource scheduling algorithms being utilized in the virtualization industry and compare them on common factors to discern the comparatively optimal resource scheduling algorithm.